Dinamika Pemilihan Kepala Desa : Studi Atas Kecenderungan Rezim Politik dalam Pelaksanaan UU No. 6 Tahun 2014 (Desa Huta Tinggi) Perspektif Siyasah Dusturiyah - Al Fauzan, Zaid; Irwansyah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The Village Head Election (Pilkades) is a concrete manifestation of the implementation of democracy at the local level as stipulated in Law Number 6 of 2014 concerning Villages. However, in practice, the dynamics of the Pilkades often show a tendency for political regime intervention, which has an impact on reducing the principle of people's sovereignty in the village. This research examines Huta Tinggi Village as a case study to examine how Pilkades regulations are implemented and to assess the extent to which local political practices are influenced by the regime's interests. Using qualitative methods through case studies, in-depth interviews, observations, and legal document analysis, this study aims to analyze political tendencies in the implementation of the Pilkades, assess the effectiveness of the implementation of the Village Law, and examine its suitability with the perspective of siyasah dusturiyah which emphasizes justice, openness, and public participation. The results show that the implementation of the Pilkades in Huta Tinggi Village shows a pattern of dominance of the local political regime that influences the nomination mechanism, mass mobilization, and the voting process. This gives rise to problems in the form of money politics, social divisions, and the weakening of the legitimacy of village leadership. From a political and economic perspective, this phenomenon reflects a deviation from the fundamental values ​​of village governance, which should be oriented toward the public interest (al-mashlahah), justice ('adl), and public participation (shura). Therefore, the Village Head Election (Pilkada) can be understood not only as an administrative process but also as an arena for political contestation fraught with regime interests. Therefore, strengthening regulations and internalizing the values ​​of political and economic governance are necessary to ensure that village democracy truly operates in accordance with the principle of popular sovereignty.